2019
DOI: 10.1108/ijebr-12-2017-0501
|View full text |Cite
|
Sign up to set email alerts
|

How families shape women’s entrepreneurial success in Morocco: an intersectional study

Abstract: Purpose Studies on women’s entrepreneurship in Morocco are scarce, despite the potential of women for the country’s economy. This research takes place in a socio-cultural environment searching for a compromise between tradition and modernity. Families occupy a prominent place in Morocco, directly influencing women’s activities. The purpose of this paper is to investigate the role of family in Moroccan women’s entrepreneurial success. Design/methodology/approach The qualitative research is based on 60 intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 72 publications
2
49
0
3
Order By: Relevance
“…Nevertheless, whereas the literature (Amine & Staub, 2009; Constantinidis et al, 2019; Mehtap et al, 2017) has established that domestic responsibilities and childcare activities exert a negative impact on women's ventures, this research substantially contributes to the understanding by providing different views. For example, the existing literature demonstrates that the household responsibilities cannot be reduced on the grounds of income‐generating activities of women (Al‐Dajani & Marlow, 2010), but this article provides a contrasting view with an atypical example of a woman's household work experiences during the unusual conditions of the pandemic period.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, whereas the literature (Amine & Staub, 2009; Constantinidis et al, 2019; Mehtap et al, 2017) has established that domestic responsibilities and childcare activities exert a negative impact on women's ventures, this research substantially contributes to the understanding by providing different views. For example, the existing literature demonstrates that the household responsibilities cannot be reduced on the grounds of income‐generating activities of women (Al‐Dajani & Marlow, 2010), but this article provides a contrasting view with an atypical example of a woman's household work experiences during the unusual conditions of the pandemic period.…”
Section: Discussionmentioning
confidence: 86%
“…Her husband helped Kiron regarding her lack of skill that was associated with her gender identity. Existing studies (Barragan, Erogul, & Essers, 2018; Constantinidis et al, 2019; Jaim, 2020a) also support the assisting roles of husbands in operating businesses of women in the highly patriarchal context.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The MENA region is male dominated, a factor underlying the increased attention to female entrepreneurship in extant research. Support from parents and spouses plays a central role in women’s entrepreneurial success (Constantinidis et al , 2018). For instance, in Morocco, Welsh et al (2017) have found that family support is the key success factor for female entrepreneurs, as such support allows them to improve their management skills and build their self-confidence.…”
Section: Resultsmentioning
confidence: 99%
“…IPA can facilitate entrepreneurship stakeholders to narrate their stories in their natural context (Steyaert, 1997), and give meaning to their experiences (Constantinidis et al, 2019). This helps scholars to appreciate that each entrepreneurial endeavour is a unique story (Blundel and Lockett, 2011), rather than a set of predefined or predictable patterns (Steyaert, 1997).…”
Section: Ipa For Entrepreneurship Researchmentioning
confidence: 99%